Mise en débat de la figure de l'expert dans les échanges en ligne sur les changements climatiques: héros, anti-héros et représentations de la science - Baptiste Campion (VertigO)
This paper presents an exploratory study of the representations of science and scientists in online debates about Global Warming between non-scientists. We analysed qualitatively and in an comprehensive manner the exchanges held in two websites discussing so-called "skeptic" theses. Results show that debates occur in very small and active communities that develop quite well-structured argumentation. Skeptics claim to produce a true scientific discourse, and develop a representation where science skeptical scientists embody the scientific ideal face of scientific institutions and researchers perceived as corrupted and driven by ideology. Opponents to skeptical positions highlight sêcific mechanisms of the scientific literature to deny to skeptics the status of experts.